Path construction techniques for dynamic control of kanban systems - Liberatore, G.; Nicosia, S.; Valigi, P. (Proceedings of 1995 34th IEEE Conference on Decision and Control, 1995)
In this paper a path construction method for discrete event dynamic systems, based on finite perturbation analysis rules, has been applied to the study of the effects of buffer size perturbations on the performance measure of a kanban system. The method has been used to build up an online strategy to control the buffering capacity of some working centres, in a multi part-type manufacturing system, subject to unknown changes in the product mix.